Glacial and Pleistocene geology. - Flint, Richard Foster 1902- (New York Wiley, 1957)
Revised and augmented edition of author's "Glacial geology and the pleistocene epoch", New York, 1947.
Based on the author's Glacial geology and the Pleistocene epoch.
Bibliography: p. 510-544.
Also issued online.
Keywords: Geology, Stratigraphic -- Pleistocene; Glaciology